2020
DOI: 10.21203/rs.3.rs-78072/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bone Marrow Mesenchymal Stem Cells Derived miRNA-130b Enhances Epithelial Sodium Channel by Targeting PTEN

Abstract: Aims: Acute lung injury (ALI) is a clinical syndrome with high morbidity and mortality, and severe pulmonary edema is one of the characteristics of ALI. Epithelial sodium channel (ENaC) located on the apical side of alveolar type 2 epithelial (AT2) cells is the primary rate limiting segments in alveolar fluid clearance. Many preclinical studies have revealed that mesenchymal stem cells (MSCs) based therapy has great therapeutic potential for ALI, while the role of ENaC in this process is rarely known. Methods:… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…However, lipoxin A4 (LXA4) treatment enhances the ENaCγ expression and promotes AFC via miR-21/PTEN/Akt pathway to protect against LPSinduced ALI [62]. In contrast, Zhang et al suggested that PTEN repression by miR-130b in BMSCs can promote the expression of ENaC alpha and gamma, which regulates severe pulmonary edema in ALI [63].…”
mentioning
confidence: 99%
“…However, lipoxin A4 (LXA4) treatment enhances the ENaCγ expression and promotes AFC via miR-21/PTEN/Akt pathway to protect against LPSinduced ALI [62]. In contrast, Zhang et al suggested that PTEN repression by miR-130b in BMSCs can promote the expression of ENaC alpha and gamma, which regulates severe pulmonary edema in ALI [63].…”
mentioning
confidence: 99%